The role of the lateral hypothalamus and orexin in ingestive behavior: a model for the translation of past experience and sensed deficits into motivated behaviors - Hurley, Seth W.; Johnson, Alan Kim (Frontiers in Systems Neuroscience, 2014)
The hypothalamus has been recognized for its involvement in both maintaining homeostasis and mediating motivated behavior. The present article discusses a region of the hypothalamus known as the lateral hypothalamic area (LHA). It is proposed that brain nuclei within the LHA including the dorsal region of the lateral hypothalamus (LHAd) and perifornical area (PeF) provide a link between neural systems that regulates homeostasis and those that mediate appetitive motivated behaviors. Functional and immunohistochemical data indicate that the LHA promotes many motivated behaviors including food intake, water intake, salt intake, and sexual behavior. Anatomical tracing experiments demonstrate that the LHA is positioned to receive inputs from brain areas involved in regulating body fluid and energy homeostasis. Regions within the LHA send dense projections to the ventral tegmental area (VTA), providing a pathway for the LHA to influence dopaminergic systems generally recognized to be involved in motivated behaviors and their reinforcement. Furthermore, the LHA contains neurons that synthesize orexin/hypocretin, a neuropeptide that promotes many appetitive motivated behaviors. The LHA also receives inputs from brain areas involved in reward-related learning and orexin neuron activation can become conditioned to environmental stimuli that are associated with rewards. Therefore, it is hypothesized that the LHA integrates signaling from areas that regulate body fluid and energy balance and reward-related learning. In turn, this information is “fed into” mesolimbic circuitry to influence the performance of motivated behaviors. This hypothesis may foster experiments that will result in an improved understanding of LHA function. An improved understanding of LHA function may aid in treating disorders that are associated with an excess or impairment in the expression of ingestive behavior including obesity, anorexia, impairments in thirst, salt gluttony and salt deficiency.